Analisis Penggunaan “Gadget” terhadap Prestasi Siswa Kelas X di SMK YPK Imanuel Kota Sorong - Simson Mambraku; Muhammad Ali Kasri; Saharudin Saharudin (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2025)
This research aims to analyze the problem or impact of using gadgets on the achievement of student X at YPK Imanuel Vocational School, Sorong City. The research method uses a qualitative approach using case studies. Data was collected by observation, interviews and documentation. The sample was determined using the